Penanaman Nilai-nilai Pendidikan Berwawasan Multikultural di Masa Pandemi - Izza, Salsa Nurul; Astuti, Amri Indri; Purwaningrum, Dilla Sekar Ayu; Rimadhani, Mira Ifta; Mahardhika, Muhammad Fajrul (YASIN, 2022)
Pancasila Education and Citizenship Education play a crucial role in instilling multicultural values in students. However, during this pandemic, there are obstacles in teaching and implementing multicultural insights. The writing of this article aims to educate how to face challenges in strengthening educational values with multicultural insight during a pandemic. This research uses the library method. The results of this study are that the inculcation of multicultural-minded values can be carried out in various ways, one of which is strengthening values in multicultural-minded education during the pandemic. Approaching students can be done by providing guidance on multiculturalism even though online and always in collaboration with guardians. students to realize the inculcation of solid multicultural values during the pandemic.